Education as a Solution: Understanding Religious Figures' Perspectives on Joint Property Division in East Lombok - Hasan, Muh. Zaki; Masnun, Masnun; Khaldun, Rendra (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study explores the perspectives of religious figures regarding joint property division in East Lombok, aiming to elucidate the role of education as a potential solution in addressing related challenges. Employing a qualitative research approach, data was collected through semi-structured interviews with key religious figures in the region. These interviews were transcribed and analyzed thematically to identify recurring patterns and themes. The findings reveal a nuanced understanding among religious figures regarding joint property division, influenced by cultural, social, and religious factors. Education emerged as a central theme in their perspectives, highlighting its potential to foster understanding, tolerance, and equitable solutions. The implications of these findings underscore the importance of integrating educational initiatives into discussions and practices related to joint property division in East Lombok, thereby promoting social cohesion and conflict resolution.